Pengaruh Desain Eksterior, Desain Interior, dan Suasana Toko Terhadap Kepuasan Pelanggan Giant Express Sindang Barang - Mulyana, Muhamad; Fadillah, Adil (Jurnal Ilmiah Manajemen Kesatuan, 2017)
The exterior design of a building is part of the physical facilities that have a role in providing location and attracting consumers to come. It is instrumental in communicating information about what is in the building as well as establishing permanent advertisement for the consumer on overall image of a retail appearance. It is necessary to maintain the balance of the image formed on the outside of the building. Some components that can be defined for the interior are the aesthetics and design space. The purpose of doing this study is to determine the extent of the influence of Exterior Design, Interior Design and Atmosphere Store for Customer Satisfaction. Customer satisfaction means that the customers must have what they really want (want), when (when), and how they acquire it. This study uses a quantitative research approach, and the data are collected by setting the first draft as the variables associated derived from existing theories obtained by researchers and use questionnaires to measure variables. Survey method used for the sampling of the population and questionnaires as main data collection instrument. SPSS is used to analyze the descriptive statistics. The result shows that exterior design has a significance impact on customer satisfaction. The interior design has an influence on customer satisfaction. The atmosphere of the store has an influence on customer satisfaction, with the regression equation is Y (16 249) = X1 (0086) + X2 (-0048) + X3 (0665).